The Origins of the Idea of “Civilizational” Multipolarity in Russian Religious Thought (from 19th to First Half of 20th Century) - M. M. Medovarov (Vestnik MGIMO-Universiteta, 2024)
The article explores the development of the concept of «civilizational» multipolarity in Russian religious thought from the 19th century to the first half of the 20th century. This notion of «civilizational» multipolarity suggests that power centers, beyond forming a geopolitical balance, also represent distinct civilizations. During the first half of the 19th century, Russian conservatism was predominantly Eurocentric and semi-colonial. However, in the latter half of the century, Russian religious thinkers began to recognize the plurality of civilizations and their potential to emerge as independent power centers, thereby reevaluating Russia's role in the world. Thinkers like Nikolay Danilevsky, Vladimir Lamansky, and Konstantin Leontyev progressively moved away from a colonial mindset, leading to the crystallization of the idea of «civilizational» multipolarity.At the turn of the 19th and 20th centuries, thinkers such as Vladimir Gringmut, Lev Tikhomirov, Prince Esper Ukhtomsky, and Sergey Syromyatnikov further advanced these ideas. They identified an «awakening of the East» and advocated for Russia to align with Eastern civilizational powers in anticipation of an imminent world war. Post-1917 revolution, the concept of «civilizational» multipolarity persisted in the Eurasianist thought of the 1920s and 1930s, which is a focal point of this article. Leaders of the Eurasianist movement, such as Prince Nikolay Trubetskoy and Petr Savitsky, developed the doctrine of autarkic «worlds»-civilizations, envisioned as large economic blocs unified by common culture, ideology, and centralized authority. Religious ideas and rhetoric, including the trope of «Babylonian confusion», played a significant role in the Eurasianists' justification of their preferred international order.